Analisis Wacana Kritis terhadap Tagline “Indonesia Gelap” dalam Berita Detik.com - Naswa Dwi Putri Nasution; Najwa Naila; Siti Fadilla Siagian; Syairal Fahmy Dalimunthe (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study employs Critical Discourse Analysis (CDA) based on Theo van Leeuwen's model to examine the representation of social actors in Detik.com's news article titled